2005
DOI: 10.1111/j.1075-122x.2005.21643.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Knowledge of Mammography Findings on the Accuracy of Breast Ultrasound in Symptomatic Women

Abstract: Breast ultrasound is generally interpreted with knowledge of the mammographic examination. This study examined the influence of knowledge of mammography findings on the accuracy of ultrasound in women with breast symptoms. Subjects were sampled from all women 25-55 years of age consecutively attending a breast clinic. This included all 240 women shown to have breast cancer and 240 age-matched women shown not to have cancer. Ultrasound films were prospectively reviewed and reported by two radiologists independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
1
17
1
Order By: Relevance
“…In a review of 22 studies Flobbe et al [7] found that ultrasound performed better than mammography in 4 of 10 studies in which prior knowledge of mammography results were available and in 8 of 11 studies in which ultrasound was interpreted independently. Their results indicate a higher relative diagnostic performance when no prior knowledge of mammography was available; however, this has not been corroborated by other investigators [8]. As well as calculating individual test performance we have shown that the addition of mammography increased sensitivity by 18.3% over clinical examination and that the addition of ultrasound further raises sensitivity by 9.8%.…”
Section: Discussioncontrasting
confidence: 76%
“…In a review of 22 studies Flobbe et al [7] found that ultrasound performed better than mammography in 4 of 10 studies in which prior knowledge of mammography results were available and in 8 of 11 studies in which ultrasound was interpreted independently. Their results indicate a higher relative diagnostic performance when no prior knowledge of mammography was available; however, this has not been corroborated by other investigators [8]. As well as calculating individual test performance we have shown that the addition of mammography increased sensitivity by 18.3% over clinical examination and that the addition of ultrasound further raises sensitivity by 9.8%.…”
Section: Discussioncontrasting
confidence: 76%
“…In studies of mammography and ultrasound for the diagnosis of breast cancer, providing clinical history improved accuracy. 2,3 However, the effect was small, with an increase in the area under the ROC curve of only 2% or 3%. In a systematic review, 9 studies assessed the effect on ROC curves of using actual history.…”
Section: Discussionmentioning
confidence: 95%
“…2 Similarly, breast ultrasonography was found to be slightly more accurate when reported with access to mammograms. 3 The accuracy of screening mammography was found to be unaltered when radiologists were supplied with clinical history. 4 However, clinical history had adverse effects on recommendations for further tests to identify cancer.…”
Section: Objectivementioning
confidence: 99%
“…All of the 240 women who had cancer, and 233 of the women who did not have cancer, underwent both tests. The study was conducted as a component of the Sydney Breast Imaging Accuracy Study, and full details of the subjects' symptoms and histological classification have been published elsewhere [6,7].…”
Section: 2mentioning
confidence: 99%